1990
DOI: 10.1017/s002221510011429x
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana smoking as a possible cause of tongue carcinoma in young patients

Abstract: A case of T1N0M0 carcinoma of the tongue in a male 23-year-old 'regular' marijuana smoker is described. Hemiglossectomy and complete bilateral neck dissection were carried out. No post-operative radiotherapy was given as the resection margins were histologically negative. The tumour recurred one year later in the left cervical region involving the mandible and surgery was again performed, but after three months, neck disease was still evident. The case described case implies the introduction of marijuana as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…Many studies also demonstrated that tetrahydrocannabinol has carcinogenic properties and that it also inhibits the functions of the immune system. 14 Authors like Darling and Arendorf in 1993 15 and Almadori et al 16 described the relationship between marijuana smoke and oral cancer and precancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies also demonstrated that tetrahydrocannabinol has carcinogenic properties and that it also inhibits the functions of the immune system. 14 Authors like Darling and Arendorf in 1993 15 and Almadori et al 16 described the relationship between marijuana smoke and oral cancer and precancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The mechanism by which marijuana smoke acts as a carcinogen relates to the presence of aromatic hydrocarbons, benzopyrene and nitrosamines 28,30 in amounts 50 per cent greater than the same amount of tobacco smoke. 13 Marijuana smoke is associated with dysplastic changes within the epithelium of the buccal mucosa (anucleated squamous cells, immature cell forms, increased nuclear pleomorphism and increased mitotic activity and abnormalities).…”
Section: Cannabis Use and Oral Cancermentioning
confidence: 99%
“…This relates to the tumours being more aggressive in younger patients, requiring more radical treatment such as widespread resection and radiotherapy. 30 A synergistic effect between tobacco and marijuana smoke has been observed, suggesting the interactions of different risk factors further increases the risk of developing oral cancer. 29 The association between the presence of oral papilloma and cannabis smoking may be related to suppression of the immune response by cannabis 26 but the human papilloma virus may also play an important role.…”
Section: Cannabis Use and Oral Cancermentioning
confidence: 99%
“…Déjà signalée par Almadori [55] en 1990 en Italie, la consommation de marijuana fait actuellement l'objet d'études aux États-Unis pour expliquer l'augmentation des cas chez les adultes de moins de 40 ans atteints de cancer des VADS, en particulier de la langue mobile [7]. Ces études épidémiologi-ques sont appuyées par des données expérimentales sur des modèles animaux [56].…”
Section: Cannabisunclassified